2010
DOI: 10.2109/jcersj2.118.1166
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of scandium aluminum nitride thin films by using scandium aluminum alloy sputtering target and design of experiments

Abstract: Scandium aluminum nitride alloy (Sc x Al 1¹x N) thin films were prepared using rf magnetron sputtering with a scandium aluminum alloy (Sc 0.42 Al 0.58 ) target on n-type (100) silicon substrates. We have investigated the effects of 4 sputtering control factors, which are substrate temperature, sputtering pressure, nitrogen (N 2 ) concentration and cathode power, on the piezoelectric constant d 33 of Sc x Al 1¹x N films using design of experiments. Consequently, it is statistically proved that N 2 concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 21 publications
1
36
0
1
Order By: Relevance
“…55 For high throughput industrial processes, a single source using an alloy target is preferred. Such processes were successfully applied with either RF 56 or dc pulsed power supplies. 57 It was found in Note: SQS, special quasi-random structure, which describes a method to handle alloy properties.…”
Section: Doped Aln Fi Lmsmentioning
confidence: 99%
“…55 For high throughput industrial processes, a single source using an alloy target is preferred. Such processes were successfully applied with either RF 56 or dc pulsed power supplies. 57 It was found in Note: SQS, special quasi-random structure, which describes a method to handle alloy properties.…”
Section: Doped Aln Fi Lmsmentioning
confidence: 99%
“…Subsequent studies took one of two directions: epitaxial stabilization of the rocksalt structure for x > 0.5 with interest in the electronic structure [4] or effects of alloying on piezoelectric properties of the wurtzite phase for x < 0.5 [5]. After increases in the longitudinal piezoelectric strain coefficient (d 33 ) were reported by Akiyama et al, the majority of the reported efforts focused on the effect of deposition parameters on crystal quality [6][7][8][9][10], residual stress [11,12], dielectric properties [6,7,13], and overall electromechanical response [11,14,15]. Motivated by industrial interest in the improved performance in AlN-based piezoelectric microelectromechanical systems (piezoMEMS) devices, the breadth of this work was focused on compositions with 0 < x < 0.4, where single-phase textured wurtzite materials could be synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that scandium aluminum (ScAl) alloy targets are effective for keeping scandium concentration constant in ScAlN thin film [15], therefore in this series of experiments, a 99.99 % pure ScAl alloy target (110 mm in diameter, quality component proportion Sc:Al = 0.1:0.9) was applied. To ensure clean surface for film growth, the sapphire substrates were successively cleaned in ultrasonic baths of acetone, absolute ethyl alcohol and deionized water for 20 min respectively and then dried with dry nitrogen before deposition.…”
Section: Methodsmentioning
confidence: 99%